Dengki, Bersyukur dan Kualitas Hidup Orang yang Mengalami Psikosomatik - Ila Nurlaila Hidayat; Witrin Gamayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
This study aims to determine the correlation of envy and gratitude to the quality of life of people who experience psychosomatic. The research uses correlational quantitative methods. The research subjects consisted of 106 students who experienced psychosomatic disorders. Measuring instruments used the Islamic Envy Scale (IES) and the Islamic Gratitude Scale (IGS) which are constructed based on the concept of envy and gratitude according to Al-Ghazali, as well as the WHO quality of life scale that was adapted. The results of multiple linear regression tests show that envy and gratitude have a significant correlation to the quality of life. More specifically, envy does not have negative correlation with the quality of life, while gratitude has positive correlation to the quality of life of people who experience psychosomatic.